EFEKTIVITAS SENAM HAMIL TERHADAP PENURUNAN DERAJAT EDEMA KAKI PADA IBU GRAVIDA TRIMESTER II DAN III - Suci Anggraeni; Yunita Febriana sari (STRADA : Jurnal Ilmiah Kesehatan, 2016)
Leg edema is one of the changes that occur during pregnancy is often a complaint of the mother gravida. Leg edema is caused because no smoothening the flow of blood at the foot. By doing pregnancy exercise regularly can improve blood circulation. This study aims to determine the effect of pregnancy exercise to decrease the degree of leg edema in the mother Gravida trim ester II and III. This study used a pre-experimental design with using one group pre-post test approach. This population was Capital gravida Trimester II and III physiologically leg edema in Pustu Lirboyo of Kediri as many as 17, while the samples used partly Capital Gravida Trimester II and III as many as 16 people using Random Sampling technique. The results showed 16 respondents before pregnancy exercise most of the level of edema in grade 2 of 8 people (50%) and after pregnancy exercise most of the level of edema in grade 1 as many as 12 people (75%). Results of data analysis obtained using the Wilcoxon test p value = 0.000, because the p value 0.000 <0.05, which means there is a pregnancy exercise influence on the degradation of leg edema mother gravida trimester II and III. By doing regular pregnancy exercise during pregnancy it will indirectly affect the blood circulation of the mother. To that can reduce leg edema in the mother gravida trimester II and III.